Hukum Adat Perkawinan Dayak Mualang Dan Perbandingannya dengan Perkawinan Gereja Katolik - Nikodemus, Nikodemus; T, Meriyadi; Hermanto, Hermanto; Endi, Yohanes (Borneo Review, 2023)
marriage of the Catholic Church. The methodology used in compiling the writing, among others, is the study of literature or literature. There are several findings that became the result of this paper. First, the Mualang Dayak are an Ibanic Dayak sub-tribe that has a variety of uniqueness, including the matter of customary law for the Mualang Dayak marriage. Second, the customary law of Mualang Dayak marriage has several laws that must be implemented, namely the Marriage Process, Forms of the Mualang Dayak Marriage Party, Forms of Violations and Penalties for Dayak Mualang Marriage. Catholic marriages of men and women become one in a holy marriage. According to the specific nature of its nature, it is directed at the goodness of husband and wife as well as the birth of children and the education of children. So Catholic marriages are elevated to a sacred dignity as the Sacrament of Marriage.